Unpacking the complex relationships between agricultural investments and biodiversity in Ghana - Abdul-Hanan Abdallah (Societal Impacts)
The expansion of large-scale agricultural investments (LSAI) in Ghana has substantial implications for biodiversity and rural community well-being. This study explores the complex relationships between LSAI and biodiversity, focusing on species richness, evenness, Enhanced Vegetation Index, and Soil Adjusted Vegetation Index to assess ecosystem health. Using a mixed-methods approach, we combine panel datasets, remote sensing, and qualitative data to evaluate both ecological and social impacts of LSAI. While LSAI has potential economic benefits, it also poses risks to biodiversity by reducing species diversity and altering ecosystem services essential for rural communities' livelihoods. Our findings reveal that while LSAI increase vegetation cover and species evenness, they frequently lead to the loss of access to critical resources such as fuelwood, medicinal plants, and wild foods, impacting community resilience and social cohesion. These findings underscore the importance of balancing agricultural investments with policies that preserve biodiversity and maintain social equity, ensuring that long-term societal impacts of LSAI do not compromise ecosystem or local livelihoods. It calls for robust monitoring systems, and the inclusion of local communities in decision-making to ensure sustainable development. The study offers critical insights for policymakers and conservationists aiming to harmonize economic development with environmental conservation in Ghana and beyond.